Strategi Pemasaran Hewan Qurban Pt Mahir Farm Nusantara di Masa PPKM - Aulia Miftahunnisa Exa Putriyana; Reny Sukmawani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Putriyana AME, Sukmawani R. 2021. Marketing strategy of livestock for qurbat at pt mahir farm nusantara during PPKM. In: Herlinda S et al. (Eds). Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 445-450. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).PPKM is a government program that regulates restrictions on community activities in Indonesia during the Covid-19 pandemic. Since the beginning of the pandemic, Indonesia has begun to be unsettled by various sectors, one of which is the economic sector. Covid-19 hit the Indonesian economy very drastically, especially when the PPKM was implemented. Many economic sectors are disrupted and unable to operate because they depend on each other, one of which is the agricultural sector. The determination of the PPKM coincides with the Eid al-Adha, wherein during this period there will be an increase in the demand of livestock for qurban. This has an impact on the demand and supply of livestock due to restrictions on activities. This study was conducted to determine the marketing strategy livestock for qurban during the PPKM period, using qualitative methods from descriptive data. Data collection techniques in this study were carried out by observing PT Mahir Farm Nusantara (MFN). The results of the study present a discussion of the marketing strategy. The strategy carried out by MFN is the implementation of the 4Ps (Product, Promotion, Price, and Place). The product strategy is in the form of qurban distribution innovation, the promotion strategy is in the form of discounts, the price strategy is that every buyer has the opportunity to get a discount or cashback, and the place strategy is flexible in product delivery, so as to maintain and improve product quality. With this innovation strategy, it can suppress the decline in total sales at PT Mahir Farm Nusantara during the PPKM period.